Yield components of the triticale collection material in the environments of the Middle Amur region - K. V. Zenkina; T. A. Aseeva (Труды по прикладной ботанике, генетике и селекции)
Background. Development of new highly adaptable triticale cultivars with high yield potential and environmental resistance to adverse factors of the Middle Amur region requires a study of the collection material. One of the priorities of such research is to identify effective sources and donors among triticale accessions according to the main yield components and economically useful traits.Materials and methods. The material was represented by spring triticale cultivars from the collection of the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR).Results. The following cultivars were identified as promising breeding sources: ‘AC Certa’, ‘Lana’, ‘Zolotoy Grebeshok’ and ‘Ulyana’ for their optimal yield in the Middle Amur region; ‘AC Certa’, ‘Zolotoy Grebeshok’, ‘Mykola’, ‘Korovai Kharkivsky’ and ‘Victoria’ for earliness; ‘Victoria’, ‘Rovnya’, ‘Kobzar’ (Ukraine), ‘Losinovske’, ‘Zgurivsky’ and ‘Sandio’ for plant height; ‘Lotos’, ‘Yarilo’, ‘ZG 186’, ‘Oberig Kharkivsky’, ‘Tleridal’ and ‘Sandio’ for ear length; ‘Lana’, ‘Ulyana’, ‘Lotos, ‘Yarilo’, ‘ZG 186’, ‘Pamyat Merezhko’, ‘Victoria’, ‘Kobzar’, ‘Oberig Kharkivsky’, ‘Tleridal’ and’ Sandio’ for the number of spikelets per ear; ‘AC Certa’, ‘Lana’, ‘Dagvo’, ‘Pamyat Merezhko’ and ‘Kobzar’ for the number of grains per ear; ‘Ukro’, ‘Lotos’, ‘Yarilo’, ‘Rovnya’ and ‘Kobzar’ for grain weight per ear; ‘Ukro’, ‘Skory’ and ‘Rovnya’ for grain size; ‘Ukro’, ‘Skory’ and ‘Rovnya’ protein content in grain; ‘Dagvo’, ‘Kobzar’ and ‘Sandio’ for lysine content in grain; ‘AC Certa’, ‘Lana’, ‘Skory’, ‘Lotus’, ‘Yarilo’, ‘ZG 186’, ‘Pamyat Merezhko’, ‘Victoria’, ‘Rovnya’, ‘Kobzar’, ‘Losinovske’, ‘Zgurivsky’, ‘Oberig Kharkivsky’, ‘Tleridal’ and ‘Sandio’ for resistance to lodging; ‘Lana’, ‘Pamyat Merezhko’, ‘Victoria Zgurivsky’, ‘Oberig Kharkivsky’ and ‘Tleridal’ for disease resistance.Conclusion. The selected accessions can be used in breeding programs of the Middle Amur region and other regions of the country.